(untitled) (Scientific journal of the Fergana State University, 2026)
This article is dedicated to the philosophical analysis of the teachings of Yusuf Khаs Hаjib, a prominent thinker of the 11th century. In his work “Kutadgu Bilig”, he addresses issues of metaphysics, epistemology, politics, and ethics, describing the ideal society based on justice, knowledge, and wisdom. The study highlights the relationship between his ideas and the philosophy of Avicenna, Farabi, and the Mashshaiya school. The authors emphasize the role of knowledge in governance and personal development, grounding political rule on ethics and wisdom. Yusuf Khаs Hаjib views knowledge as a vital means of forming a perfect individual and a stable society, stressing the importance of ethics, justice, and wisdom in his work. He proposes an ideal model of governance based on logic and experience, closely resembling the teachings of major Islamic philosophers. This article explains Yusuf Khаs Hаjib’s contribution to Islamic philosophy and the medieval culture of Turkistan using a comparative analysis method and primary sources.